New Financial Technologies: New Opportunities and New Challenges of the XXI Century - Nurgazina, A.; Doszhan, R.; Sabidullina, A. (Journal of Economic Research & Business Administration, 2021)
Financial technology, or “Fintech”, is a sphere comprising from firms which are related to technology, and work in order to create a competitive environment for existing financial companies, and to create new services in the markets. Fintech is created in order to offer new convenient solutions in the financial environment. On the one hand, these innovations work and bring high profits to the creators. Fintech provides an opportunity for renewed activity in underdeveloped markets that are less attractive to investors, especially in today’s environment (for example, money transfers). On the other hand, such a drive motivates to create innovations in the financial markets. Organizations built on these models are now at the forefront of the modern technologies in finance. The actual reason of this article is to find and show the nature of the modern concept, trends, and challenges for new financial technologies in Kazakhstan and abroad. The article discusses the financial technologies concepts and their impact on to the economy; analyzes the main indicators of financial technology development in Kazakhstan mostly in the banking sector. The article explores the theoretical and methodological foundations of modern Fintech process based on the analysis of relevant works in this field of study. Issues of modern references, magazines, and Internet resources were used for the research. The theoretical and practical significance of this work determines a wider range of disclosure of the basic conceptual apparatus and the search for modern ways to use the results in the activities of various institutions for the development of measures to improve them. Key words: financial technologies, digital technologies, mobile wallets, P2P.